Chemo‐small extracellular vesicles released in cisplatin‐resistance ovarian cancer cells are regulated by the lysosomal function - Cerda Troncoso, Cristóbal (2024)
Chemoresistance is a common problem in ovarian cancer (OvCa) treatment, where resistant cells, in response to chemotherapy, secrete small extracellular vesicles (sEVs), known as chemo-sEVs, that transfer resistance to recipient cells. sEVs are formed as intraluminal vesicles (ILVs) within multivesicular endosomes (MVEs), whose trafficking is regulated by Ras-associated binding (RAB) GTPases that mediate sEVs secretion or lysosomal degradation. A decrease in lysosomal function can promote sEVs secretion, but the relationship between MVEs trafficking pathways and sEVs secretion in OvCa chemoresistance is unclear. Here, we show that A2780cis cisplatin (CCDP) resistant OvCa cells had an increased number of MVEs and ILVs structures, higher levels of Endosomal Sorting Complex Required for Transport (ESCRTs) machinery components, and RAB27A compared to A2780 CDDP-sensitive OvCa cells. CDDP promoted the secretion of chemo-sEVs in A2780cis cells, enriched in DNA damage response proteins. A2780cis cells exhibited poor lysosomal function with reduced levels of RAB7, essential in MVEs-Lysosomal trafficking. The silencing of RAB27A in A2780cis cells prevents the Chemo-EVs secretion, reduces its chemoresistance and restores lysosomal function and levels of RAB7, switching them into an A2780-like cellular phenotype. Enhancing lysosomal function with rapamycin reduced chemo-sEVs secretion. Our results suggest that adjusting the balance between secretory MVEs and lysosomal MVEs trafficking could be a promising strategy for overcoming CDDP chemoresistance in OvCa.